Survival trade-offs in plant roots during colonization by closely related beneficial and pathogenic fungi - Stéphane Hacquard (Nature Portfolio, 2016)
Colletotrichum tofieldiae is a beneficial root endophyte, whereas the closely related C. incanumis pathogenic. Here the authors compare the genomes and transcriptomes during host plant interaction and demonstrate that the host plant can respond differently to the beneficial endophyte according to phosphate status.